THE MOTHERING PRACTICES OF THE CAREGIVER MOTHERS OF THE QOM CULTURE AS CONTENT FOR TEACHER TRAINING IN AN INTERCULTURAL PERSPECTIVE - Sylvia Edith Sandoval; Amancia Silvestre; Annek Shawny Zamora Aray (Revista del Instituto de Investigaciones en Educación, 2021)
The article aims to reflect on the results of the research project " Mothering Practices of Caregiver Mothers of the Qom Culture" (CMQC) and contrast them with the contents on family and community history delivered by the Chair of Social Sciences in Early Childhood Education of the Early Education Teacher's Degree program. It is a case study in social contexts with indigenous peoples that investigates practices used by Caregiver Mothers in the upbringing of Qom children in their community. The notions of family history and community stem from these practices. To this end, a theoretical framework with an intercultural stance was developed. We also proposed categories to analyze the characteristics of time and space in the narration of the past. In a context of socio-cultural diversity, the case study allowed us to contrast the Qom model with the generalized model of teaching family history in Creole culture and highlight the link between the narration of the past and the natural environment. However, these comparisons call for a review of hegemonic models of past narratives and places of community memory. Reflection on both aspects must be present in teacher education to promote the practice of inclusive citizenship in kindergarten.